Assessment transition of exercise and dietary habit of athletes before and during Ramadan in the pandemic of Covid-19 - Toni Kurniawan; Yetty Septiani Mustar; Agus Hariyanto; Indra Himawan Susanto; Anna Noordia (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
This study aims to identify the training transitions and dietary habits of volleyball athletes' before and during Ramadan in the Covid-19 pandemic. The research design used is descriptive quantitative with a sample of 12 male junior volleyball athletes in the academy Sidoarjo volleyball. The results showed that most athletes experienced a decrease in the frequency of exercise during the month of Ramadan, especially during the COVID-19 pandemic. A total of 33.3% of athletes maintained their exercise frequency, and 66.7% experienced a decrease in exercise frequency. Furthermore, during Ramadan and Covid-19, there was an increase in the frequency of eating 1-2 times a day (58.4%), snack consumption (50%), fruit and vegetables (75%), fried foods 4-7 times a week (8.4%), instant noodles 1-3 times a week (25%) and fast food 1-3 times a week (8.4%) in athletes. Concerning this, it is imperative to revitalize the program and monitor the athlete's training periodically, which is adjusted to the conditions of the COVID-19 pandemic and provide a dietitian to regulate the athlete's diet to obtain a balanced nutritional intake following the exercise portion.Assessmen transisi latihan dan pola makan atlet sebelum dan saat ramadan di masa pandemi Covid-19AbstrakTujuan dari penelitian ini adalah untuk mengidentifikasi transisi latihan dan pola makan atlet bola voli sebelum dan saat ramadan di masa pandemi Covid-19. Desain penelitian yang digunakan yaitu deskriptif kuantitatif dengan sampel 12 atlet laki-laki bola voli junior yang masih aktif dalam menjalani pemusatan latihan di Akademi Bola Voli Indomaret Sidoarjo. Hasil penelitian menunjukkan bahwa mayoritas atlet mengalami penurunan frekuensi latihan saat ramadan khususnya di masa pandemi covid-19. Sebanyak 33,3% yang mampu mempertahankan frekuensi latihan dan 66,7% mengalami penurunan frekuensi latihan. Selanjutnya, saat ramadan dan Covid-19 terjadi peningkatan frekuensi makan 1-2 sehari (58,4%), konsumsi camilan (50%), buah dan sayuran (75%), gorengan 4 – 7 kali dalam seminggu (8,4%), mie instant 1 – 3 kali dalam satu minggu (25%) serta makanan cepat saji 1 – 3 kali dalam seminggu (8,4%) pada atlet. Berdasarkan hal ini, maka sangat penting untuk melakukan revitalisasi program dan pemantauan latihan atlet secara berkala yang disesuaikan dengan masa pandemi covid-19 dan menyediakan dietisien untuk pengaturan makan atlet agar dapat memperoleh asupan gizi seimbang sesuai dengan porsi latihannya.